2003
DOI: 10.1128/iai.71.8.4498-4505.2003
|View full text |Cite
|
Sign up to set email alerts
|

Relative Roles of Genetic Background and Variation in PspA in the Ability of Antibodies to PspA To Protect against Capsular Type 3 and 4 Strains of Streptococcus pneumoniae

Abstract: Pneumococcal surface protein A (PspA) is able to elicit antibodies in mice and humans that can protect mice against fatal infection with Streptococcus pneumoniae. It has been observed that immunization with a single family 1 PspA can protect mice against infections with capsular type 3 or 6B strains expressing PspA family 1 or 2. However, several studies have shown that immunity to PspA is less efficacious against several capsular type 4 strains than against strains of capsular types 3, 6A, and 6B. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 35 publications
5
43
2
1
Order By: Relevance
“…In other studies using intravenous challenge with capsular type 3 and 6B pneumococci, it has been observed that cross-protection can be extended across PspA families, even though antibody cross-reactivity is weak (3,4). However, when a capsular type 4 pneumococcus was used as the challenge strain, the results were similar to those reported here; the best protection was obtained when the challenge strain and the immunizing antigen were in the same clade (22).…”
Section: Discussionsupporting
confidence: 86%
“…In other studies using intravenous challenge with capsular type 3 and 6B pneumococci, it has been observed that cross-protection can be extended across PspA families, even though antibody cross-reactivity is weak (3,4). However, when a capsular type 4 pneumococcus was used as the challenge strain, the results were similar to those reported here; the best protection was obtained when the challenge strain and the immunizing antigen were in the same clade (22).…”
Section: Discussionsupporting
confidence: 86%
“…We were able to demonstrate differences in the amounts of PspA-specific antibody that bound to different isolates. These results provide additional support for the hypothesis that the ideal PspA-based subunit vaccine should contain at least one member of each of the major PspA families in order to ensure the elicitation of protective immunity against 90% or more of pneumococci (30,39,40,48).…”
Section: Discussionmentioning
confidence: 54%
“…Namely, antigen targets up-regulated in biofilm-released bacteria were prepared as recombinant proteins and tested for protection relative to the well-established S. pneumoniae surface protein antigen (PspA), which is one of the best-studied protein protective vaccine candidates and also is up-regulated during virulence transition ( Fig. 2E) (36)(37)(38). Under these conditions, all antigens except DexB showed protection comparable to PspA, with two antigens, GlpO (an α-glycerophosphate oxidase) and PncO (a bacteriocin ABC transporter transmembrane protein), demonstrating promising individual protection surpassing that of PspA.…”
Section: Resultsmentioning
confidence: 99%